Letter to William A. Lester, Jr. from William A. Guillory, April 28, 1975 - Guillory, William A.; National Organization for Black Chemists and Chemical Engineers (1975)
Letter from William A. Guillory to William A. Lester, Jr. (1937-) inquiring the possibility of IBM sponsoring a fellowship for Black and minority students pursuing careers in science and engineering.
Keywords: Guillory, William A.; Lester, William A., Jr., 1937-; Scholarships; National Organization for Black Chemists and Chemical Engineers; African American students; College students, Black